HeberFERON in the treatment of patients with basal cell carcinoma of the ear - Vladimir Sánchez Linares; Elizabeth Brito García; Belkys Martínez Fando; Yoelvis Álvarez Gómez; Iraldo Bello Rivero (Gaceta Médica Espirituana, 2023)
Background: Basal cell carcinoma of the auricular region is one of the most aggressive cancers and with the worst prognosis, is usually destructive and mutilating, therefore conservative treatment, such as the use of interferons, is important in routine medical practice.